La representación de la violencia policial en las manifestaciones de junio de 2013: un análisis crítico del discurso de las editoriales de los diarios Folha de São Paulo y O Liberal - PERDOMO, Fernando Iván Ruiz (2017)
Despite the bombastic declared end of history in the version of liberal democracy and the capitalist system, the end of ideologies and the class struggle, the supposed consensus of humanity on human rights and progress as the north of societies and its governments in this second decade of the twenty-first century, what we witness is the irruption of varied and novel processes of political action that have shaken the world, such as the Arab Spring, the Occupy Wall Street demonstrations of Ferguson against police violence in the United States, environmental protests in Turkey, Chilean students, Colombian peasants and the Free Pass Movement in Brazil. Although their contexts and motivations are varied, each one of them represented moments of strong tension within their countries, as a result of the clashes of violence and the struggle of speeches. In this international context of social unrest, the present investigation, centered on the Brazilian case, forms part of the demonstrations of June 2013 that triggered the increase in the passage of public transport in several cities, protests that had high doses of violence and repression, with the use not only of the truculence of armed bodies destined to preserve public order, but also of the judicial system, government speeches, mass media, among others. Concomitant with the occupation of forces in the streets between demonstrators and institutional armed forces, the symbolic struggle was fought, the clash of speeches, on the one hand, legitimizing discourses of the police order and the legitimate use of force used for its preservation, for the another, discourses that question the police order that resituate the force used by the armed bodies intended to preserve public order in the context of domination, to strip it of its legitimacy and justify its actions in response to institutional violence. From the perspective of the Critical Analysis of the Discourse we will analyze the editorials of the newspapers O Liberal and Folha de São Paulo that directly or indirectly, report the police violence against the demonstrators. The reflection on the texts in context will be based on the analysis of one category and two relations, with respect to the first one, the (de) construction of the "other" will be observed through the revision of the lexicon used by the newspapers, to describe the manifestations and demonstrators, as well as the force deployed by the armed forces responsible for controlling the June demonstrations in the cities of Belém and São Paulo, if it is considered violence or law enforcement, and the justification or condemnation of it . As for relations, the nexus between the discourses and the intensity of the force exerted for the control of the manifestations, and between the discourses and relations of power produced in that context, will be analyzed.